A Study of Palm Oil as an Insulating Medium - D. Ahmad, N.; N.M. Zubir, S.; S. Ramli, S.; H. Ishak, N.; S.. Saidon, W.; Salim6, NA. (International Journal of Engineering and Technology, 2018)
A power transformer is the main component in a power system network. The most used insulating material in the transformer is mineral oil because of the high properties and best performance. Insulating oil is very important to protect transformer from any hazard condition. However, the oil can affect the environment, high in cost and unpredictable quantity because it is a natural source. The study of palm oil as insulating medium is suggested as Malaysia is the second largest country that produces palm oil. Palm oil has many benefits and easy to produce without need too much guard after the planting. The aim of this research is to study the characteristic of palm oil that can benefit as transformer oil, compare the differences of palm oil with respect to the mineral oil used in the high power transformer, and test its characteristic. Three   experiments conducted are palm oil are breakdown voltage, tan delta, and aging determination. The results show that palm oil has future to be the renewable and biodegradable alternative. As the properties of palm oil used in the transformer has maximum dielectric field strength, low tan delta and can withstand the long aging process.
Keywords: Transformer; Insulation; Breakdown Voltage; Palm Oil; Mineral Oil